2021
DOI: 10.1039/d1dt02351a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tris(3-pyridyl)aluminate ligand and its unexpected stability against hydrolysis: revealing cooperativity effects in heterobimetallic pyridyl aluminates

Abstract: We report the elusive metallic anion [EtAl(3-py)3]- (3-py = 3-pyridyl) (1), the first member of the anionic tris(3-pyridyl) family. Unexpectedly, the lithium complex 1Li shows substantial protic stability against water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Notably, this method allowed employing, at room temperature, a wide number of aryllithiums that usually require cryogenic conditions for their effective use (e. g. 3-pyridinyllithium, (3,5bis(trifluoromethyl)phenyl)lithium). [21] Moreover, the Barbiertype method requires three pumps for the reagent solutions delivery, while the need of preforming the aryllithium in a separate reactor would have required an additional pump, complicating the flow set-up.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Notably, this method allowed employing, at room temperature, a wide number of aryllithiums that usually require cryogenic conditions for their effective use (e. g. 3-pyridinyllithium, (3,5bis(trifluoromethyl)phenyl)lithium). [21] Moreover, the Barbiertype method requires three pumps for the reagent solutions delivery, while the need of preforming the aryllithium in a separate reactor would have required an additional pump, complicating the flow set-up.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Tripodal, facially coordinating tris (pyridyl) ligands have far-reaching applications in coordination, organometallic catalysis, and supramolecular chemistry. , The selection of the bridgehead atom and the position of the N-donor atoms in the pyridyl rings have a fundamental impact on the behavior and coordination properties of this family of ligands. , Classically, studies have focused on tris (2-pyridyl) ligands containing nonmetallic bridgehead atoms, E­(2-py) 3 (e.g., E = CR, COR, CH, N, P, PO; 2-py = 2-pyridyl) . However, incorporating heavier and more metallic main-group bridgehead atoms has been shown to provide an important tool for tuning the ligand character, enabling systematic modification of the bite angle, donor/acceptor properties, and reactivity. , Recent studies have explored the coordination chemistry of tris (2-pyridyl) ligands based on Sb and Bi, which coordinate metals (e.g., Cu + , Ag + , Li + ) through the three pyridyl arms in an N , N , N -chelate coordination mode, which is typical of the tris (2-pyridyl) family (intramolecular coordination, Figure a). , In addition, changing the position of the pyridyl N-donor atom from the 2- to the 3-position with respect to the bridgehead atom/group significantly changes the coordination behavior of the ligands, permitting the coordination of multiple metal centers. , The coordination of the tris (3-pyridyl) and tris (4-pyridyl) ligands to Cu and Ag salts gives extended structures involving a combination of N-donor and bridgehead-donor bonding (intermolecular coordination, Figure b). , …”
Section: Introductionmentioning
confidence: 99%
“…14,15 In addition, changing the position of the pyridyl N-donor atom from the 2-to the 3-position with respect to the bridgehead atom/group significantly changes the coordination behavior of the ligands, permitting the coordination of multiple metal centers. 16,17 The coordination of the tris (3-pyridyl) and tris(4pyridyl) ligands to Cu and Ag salts gives extended structures involving a combination of N-donor and bridgehead-donor bonding (intermolecular coordination, Figure 1b). 18,19 Despite increasing interest in this area, the elaboration of this type of ligand using extended N-donor polyaromatic donor groups has been largely ignored as a means of modifying the coordination character.…”
Section: ■ Introductionmentioning
confidence: 99%
“…34,36,37,41 In addition to varying the nature of and substituents present on the porphyrins, another potential way of modifying the dimensions and coordination characteristics of the capsules is changing the bridgehead atom present in the tris(3-pyridyl) linker unit. We have very recently developed synthetic approaches to metallic or semi-metallic tris-pyridyl ligands, [42][43][44][45][46][47] including the heavier Group 15 ligands E(3-py) 3 [E = Sb (1), Bi (2)] (Fig. 2a), 48 and shown that the latter can be employed in the construction of a series of hybrid MOF arrangements with Cu + and Ag + (=M + ) salts, in which the ligands adopt a tetradentate N,N,N,E-bonding mode.…”
Section: Introductionmentioning
confidence: 99%